SUFISM IN PUNJAB ([S.l.])
1 online resource
Keywords: This anthology is a collective endeavor of scholars from India and Pakistan devoted to Sufi mystics, literature and shrines with a detailed introduction. The essays explore the methods adopted by the Punjab Sufis to popularize the mystic ideology and praxis in the medieval socio-cultural milieu. These writings also delve into the different genres of Sufi literature, both in the elite and vernacular languages, intending to appreciate the nuances of Punjab Sufism. Apart from the architectural features of the Sufi shrines, the anthology attempts to illumine the organic linkages between these institutions and the Punjabis and, thus, underscore the Sufi non-communitarian devotion as a primary ingredient of the Punjabi cultural fusion. This title is co-published with Aakar Books. Print editions not for sale in South Asia (India, Sri Lanka, Nepal, Bangladesh, Pakistan and Bhutan)